(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Kelantan experiences annual flood events, many of which are triggered by rainfall exceeding historical norms. This study investigates the spatiotemporal patterns of rainfall and water levels in Kuala Krai, Kelantan, Malaysia, using data collected from 2009 to 2020 by the Department of Irrigation and Drainage (DID). Missing data were addressed through arithmetic mean interpolation, and trend analyses were conducted using the Mann-Kendall test. The total rainfall ranged from 28,698.3 mm to 30,610.4 mm across Dabong, Ldg. Kuala Gris, Kg. Laloh, Ldg. Lepan Kabu, Ldg. Kuala Nal, and JPS Kuala Krai, reflecting spatial variability in precipitation within the district. Among these stations, Dabong recorded the highest average monthly rainfall at 212.572 mm, followed closely by Ldg. Kuala Nal at 210.868 mm. The comparison between interpolated and missing rainfall datasets was minimal at Dabong station (average 0.286 mm; total 41.4 mm), indicating that the observed data were largely complete and reliable. By contrast, Kg Laloh station recorded the highest difference (average 7.287 mm; total 1049.3 mm), suggesting substantial gaps in the original dataset and a heavy reliance on interpolation to reconstruct rainfall values. According to the map created in the present study, the high-risk flood-prone area is concentrated in the central part of Kuala Krai, where almost 70% of the district was inundated during major flood events. The findings emphasise the significance of precise rainfall monitoring and underscore the wider effects of extreme weather on hydrological systems and community readiness.